2022
DOI: 10.1371/journal.pone.0265136
|View full text |Cite
|
Sign up to set email alerts
|

Predicting wildlife corridors for multiple species in an East African ungulate community

Abstract: Wildlife corridors are typically designed for single species, yet holistic conservation approaches require corridors suitable for multiple species. Modelling habitat linkages for wildlife is based on several modelling steps (each involving multiple choices), and in the case of multi-species corridors, an approach to optimize single species corridors to few or a single functional corridor for multiple species. To model robust corridors for multiple species and simultaneously evaluate the impact of methodologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…While elephants are known to be highly adaptable, for instance, changing their behaviours when using human-dominated landscapes (Graham et 2009), the evidence we collected from both interviews and ground tracking shows that their use of the Katavi-Mahale wildlife corridor has substantially declined. This apparent sensitivity to corridor degradation is in accordance with the findings of another study carried out in an area between Lake Manyara and Tarangire National Parks in Tanzania (Riggio et al, 2022). However, we found that other species of large mammals were still using the degraded areas between the Katavi and Mahale National Parks.…”
Section: Generalsupporting
confidence: 92%
“…While elephants are known to be highly adaptable, for instance, changing their behaviours when using human-dominated landscapes (Graham et 2009), the evidence we collected from both interviews and ground tracking shows that their use of the Katavi-Mahale wildlife corridor has substantially declined. This apparent sensitivity to corridor degradation is in accordance with the findings of another study carried out in an area between Lake Manyara and Tarangire National Parks in Tanzania (Riggio et al, 2022). However, we found that other species of large mammals were still using the degraded areas between the Katavi and Mahale National Parks.…”
Section: Generalsupporting
confidence: 92%
“…Although the target species appear widely distributed across the core PCAs in the ecosystem, they were mostly absent from the UAs (Figure 3a–f). Because large‐scale connectivity is pivotal, especially for large and wide‐ranging mammals (Cisneros‐Araujo et al, 2021; Riggio et al, 2022), we recommend targeted efforts in areas outside of protected areas to ensure functional connectivity to adjacent ecosystems in order to support the persistence of wildlife populations over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…However, overall wildlife movements within Tanzania have been constricted by rapid expansion of agriculture and human settlements (Caro & Davenport, 2016;Jones et al, 2009;Lamprey, 1964;Riggio et al, 2022;Riggio & Caro, 2017). Although savannah elephants are known to cross the GRE (Douglas-Hamilton, 1973;Lohay et al, 2020;Prins et al, 1994), most other wildlife movements eastwest or around the formidable cliffs of the GRE are rare (Baker et al, 1972;Scoon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast Masai giraffe populations in the Serengeti Ecosystem west of the GRE are dispersed over a large single, protected landscape mostly free of human settlements and agriculture, although whether giraffes move between dispersed populations in the Serengeti Ecosystem is unknown. However, overall wildlife movements within Tanzania have been constricted by rapid expansion of agriculture and human settlements (Caro & Davenport, 2016 ; Jones et al, 2009 ; Lamprey, 1964 ; Riggio et al, 2022 ; Riggio & Caro, 2017 ). Although savannah elephants are known to cross the GRE (Douglas‐Hamilton, 1973 ; Lohay et al, 2020 ; Prins et al, 1994 ), most other wildlife movements east–west or around the formidable cliffs of the GRE are rare (Baker et al, 1972 ; Scoon, 2018 ).…”
Section: Introductionmentioning
confidence: 99%